Comparing Glycemic Indices among Different Ethnic Groups Residing in Yenegoa, Bayelsa State, Nigeria - , Jonathan Nyebuchi; , Victor Tuanwii Ideede; , Felix Eedee Konne; , Fyneface Chikadibia Amadi; , Friday Ogidigba (Archives of Current Research International, 2021)
Increased prevalence and incidence rates within ethnic minorities have been reported by numerous studies on tribal differences in type 2 diabetes patients, sharing a western setting. This study was aimed at comparing glycemic indices among different ethnic groups residing in Yenegoa, Bayelsa State. The study population consisted of apparently150 healthy male and female subjects; 116 Ijaws, 21 Igbos and 13 Yorubas residing in Yenagoa Local Government Area, Bayelsa State of Nigeria. All subjects were aged between 16 and 48 years. 4 mls of Blood samples was collected from each subject. 2mls of the blood was withdrawn into EDTA for HbA1c estimation while the other 2mls was withdrawn into fluoride oxalate for fasting blood glucose. Glycated haemoglobin (HbA1c) was determined using the automated CLOVER A1c Analyser while FBG was assayed using Glucose Oxidase Method. Results revealed that there was a significant difference in the mean levels of FBG among the studied groups (P-value < 0.05) but there was no significant difference in the HbA1c mean levels (P-value > 0.05). This study has revealed that ethnic differences may cause significant changes on fasting blood glucose but may not in HbA1c.